Effect of hospitalization or surgery on dental fear in 5-10 year-old children - Naser kaviani; Leila Bahrami (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Dental fear is common in children. Many factors affect the severity of this kind of fear. Hospitalization increases children's dental fears. The aim of this study was to evaluate the effect of the type of hospitalization on children's dental fear.Materials and Methods: In this cross-sectional study, 153 children were placed in three equal groups, with a history of hospitalization, with a history of major surgery and a control group without any history of hospitalization and surgery. The children's dental fear was evaluated with Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) questionnaire. Data was analyzed with chi-squared and Kruskal-Wallis tests and one-way ANOVA (α = 0.05). Results: The means of dental fear based on CFSS-DS score were higher in hospitalization and surgery groups in comparison with the control group (p value < 0.001). Dental fear score in hospitalization group was 37.4 and higher than the two other groups. Fear from injection and dyspnea and use of dental drills were the most common causes of fear, in descending order, in the groups under study. Conclusion: Hospitalization and surgery increase children's fear of dental procedures. Dental fear in children with hospitalization in internal wards is more than the other groups, which might be attributed to frequent diagnostic and therapeutic procedures during the hospitalization period.Key words: Dental Anxiety, Hospitalization, Oral, Surgery.